1995
DOI: 10.1111/j.1600-0765.1995.tb01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of proinflammatory cytokines by human gingival fibroblasts in response to lipopolysaccharides and interleukin‐1β

Abstract: We have examined the ability of gingival fibroblasts (GF) to participate in inflammatory response and function as accessory immune cells. The accessory immune function of GF cells was evaluated by their ability to elaborate proinflammatory cytokines following stimulation with lipopolysaccharides and interleukin-1 beta (IL-1 beta). Using three separate clonally derived and characterized human gingival fibroblast (GF) cell lines, we demonstrate that LPS from Actinobacillus actinomycetemcomitans (Aa) and Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 27 publications
6
68
0
5
Order By: Relevance
“…Bacterial components of P. gingivalis, such as LPS, have also been demonstrated to have the ability to activate osteoclast formation indirectly by stimulating osteoclasts or inflammatory cells as a consequence of inducing inflammatory cytokines (9,30). Among inflammatory cytokines, IL-1 and TNF-␣ are thought to be pivotal factors in bone remodeling both in vitro and in vivo, and IL-6 has been observed in inflamed periodontal tissues (1,2,8,10,16,18). Diseased gingival tissue expressed high levels of IL-1, TNF-␣, and IL-1 receptor antagonist mRNA in the connective tissue compared to healthy gingival tissue (27,34).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial components of P. gingivalis, such as LPS, have also been demonstrated to have the ability to activate osteoclast formation indirectly by stimulating osteoclasts or inflammatory cells as a consequence of inducing inflammatory cytokines (9,30). Among inflammatory cytokines, IL-1 and TNF-␣ are thought to be pivotal factors in bone remodeling both in vitro and in vivo, and IL-6 has been observed in inflamed periodontal tissues (1,2,8,10,16,18). Diseased gingival tissue expressed high levels of IL-1, TNF-␣, and IL-1 receptor antagonist mRNA in the connective tissue compared to healthy gingival tissue (27,34).…”
Section: Discussionmentioning
confidence: 99%
“…Three different concentrations of bacteria were used for the challenge (5 ϫ 10 7 , 5 ϫ 10 8 , and 5 ϫ 10 9 /ml), and all assessments were made in triplicate. Supernatants were collected at six different time points (1,3,6,12,24, and 48 h following challenge), centrifuged (13,000 ϫ g for 5 min), and frozen in multiple aliquots at Ϫ80°C. ELISA for cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…For example, microbial factors such as LPS and cytokines such as IL-1 and TNF-␣induce IL-6 mRNA expression in fibroblasts (Agarwal et al, 1995). It has been reported that the effects of IL-1 and TNF-␣ are more involved in the regulation of IL-6 by fibroblasts rather than the direct effects of bacterial LPS (Kent et al, 1998).…”
Section: (2) Gingivalfibroblasts As Immunocompetent Cellsmentioning
confidence: 99%